PENGARUH PENAMBAHAN SARI PALA (Myristica fragrans) dan CENGKEH (Eugenia carryophyllus) TERHADAP TINGKAT KESUKAAN MINUMAN SERBUK BERBASIS LEMON CUI (Citrus microcarpa) - Mariati Edam (Balai Riset Dan Standardisasi Industri Manado, 2018)
Lemon cui, nutmeg meat and clove leaf contain antioxidants which can be added to powder drinks. The purpose of this study was to obtain the most preferred formula of lemon cui based instant powder drinks with the addition of nutmeg and clove leaf juice. This research uses descriptive method with experimental design that is Complete Random Design (CRD) with the treatment of the type of addition of nutmeg and clove leaf juice as antioxidants, as many as six levels of treatment made in the following formulations: (A) 50% sucrose: lemon cui juice 30%: water 20%; (B) 50% sucrose: 30% lemon cui juice: 0% nutmeg juice: clove juice 20%; (C) 50% sucrose: 30% lemon cui juice: 5% nutmeg juice: clove juice 15%; (D) 50% sucrose: 30% lemon cui juice: 10% nutmeg juice: clove juice 10%; (E) 50% sucrose: 30% lemon cui juice: 15% nutmeg juice: clove juice 5%; (F) 50% sucrose: 30% lemon cui juice: nutmeg juice 20%: clove juice 0%. The results showed that the percentage of panelists' preference based on indicators of color, odour and taste of lemon cui based powder drinks ranged from 57 to 67%, with preference level criteria being neutral. The organoleptic test results showed that the level of preference for color (2.76-3.68), odour (2.70-3.12) and taste (2.54-3.24) with criteria of liking. Based on the results of the study, it was concluded that the panelists' preferred level of the best lemon cui based instant powder drink was formula B.Keywords: cloves, lemon cui, nutmeg, powder drinks.